X-ray inactivation of RNA viruses without loss of biological characteristics - Babak Afrough; Jonathan Eakins; Sarah Durley-White; Stuart Dowall; Stephen Findlay-Wilson; Victoria Graham; Kuiama Lewandowski; Daniel P. Carter; Roger Hewson (Scientific Reports, 2020)
Abstract In the event of an unpredictable viral outbreak requiring high/maximum biosafety containment facilities (i.e. BSL3 and BSL4), X-ray irradiation has the potential to relieve pressures on conventional diagnostic bottlenecks and expediate work at lower containment. Guided by Monte Carlo modelling and in vitro 1-log10 decimal-reduction value (D-value) predictions, the X-ray photon energies required for the effective inactivation of zoonotic viruses belonging to the medically important families of Flaviviridae, Nairoviridae, Phenuiviridae and Togaviridae are demonstrated. Specifically, it is shown that an optimized irradiation approach is attractive for use in a multitude of downstream detection and functional assays, as it preserves key biochemical and immunological properties. This study provides evidence that X-ray irradiation can support emergency preparedness, outbreak response and front-line diagnostics in a safe, reproducible and scalable manner pertinent to operations that are otherwise restricted to higher containment BSL3 or BSL4 laboratories.